Living donor risk model for predicting kidney allograft and patient survival in an emerging economy. Issue 3 (20th February 2018) - Zafar, Mirza Naqi; Wong, Germaine; Aziz, Tahir; Abbas, Khawar; Adibul Hasan Rizvi, S.
Abstract: Aim: Living donor kidney is the main source of donor organs in low to middle income countries. We aimed to develop a living donor risk model that predicts graft and patient survival in an emerging economy. Methods: We used data from the Sindh Institute of Urology and Transplantation (SIUT) database ( n = 2283 recipients and n = 2283 living kidney donors, transplanted between 1993 and 2009) and conducted Cox proportional hazard analyses to develop a composite score that predicts graft and patient survivals. Results: Donor factors age, creatinine clearance, nephron dose (estimated by donor/recipient body weight ratio) and human leukocyte antigen (HLA) match were included in the living donor risk model. The adjusted hazard ratios (HRs) for graft failures among those who received a kidney with living donor scores (reference to donor score of zero) of 1, 2, 3 and 4 were 1.14 (95%CI: 0.94–1.39), 1.24 (95%CI:1.03–1.49), 1.25 (95%CI:1.03–1.51) and 1.36 (95%CI:1.08–1.72) ( P ‐value for trend =0.05). Similar findings were observed for patient survival. Conclusions: Similar to findings in high income countries, our study suggests that donor characteristics such as age, nephron dose, creatinine clearance and HLA match are important factors that determine the long‐term patient and graft survival in low income countries. However, other crucial but undefined factors may play a role in determining the overall risk of graft failure and mortality in living kidney donor transplant recipients. Summary at a Glance: This manuscript provides a living donor risk model for predicting patient and allograft survival, based on 2283 living kidney transplant in Pakistan.